Proactive key distribution using neighbor graphs. - Mishra, A. (IEEE Wireless communications)
User mobility in wireless data networks is increasing because of technological advances, and the desire for voice and multimedia applications. These applications, however, require that handoffs between base stations (or access points) be fast to maintain the quality of the connections. In this article we introduce a novel data structure, the neighbor graph, that dynamically captures the mobility topology of a wireless network. We show how neighbor graphs can be utilized to obtain a 99 percent reduction in the authentication time of an IEEE 802.11 handoff (full EAP-TLS) by proactively distributing necessary key material one hop ahead of the mobile user. We also present a reactive method for fast authentication that requires only firmware changes to access points and hence can easily be deployed on existing wireless networks.